2021
DOI: 10.1111/psyp.13814
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical correlates of impaired motor inhibition and outcome processing are related in high binge‐watching

Abstract: With the increasing availability of online streaming platforms, their large repertoire of shows, and policy to release entire seasons at once, binge-watching (BW)-subsequently watching multiple episodes (Trouleau et al., 2016;Walton-Pattison et al., 2018)-attracts growing theoretical and empirical interest (Schlütz, 2015). BW is a popular and rewarding leisure activity that should not be unnecessarily pathologized (Billieux et al., 2015). However, BW does entail problematic potential as it is linked to negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 92 publications
2
7
0
Order By: Relevance
“…It was directly positively associated with well-being, which is congruent with its significant association with a variety of facets of well-being, including happiness (de Ridder et al, 2012; Tangney et al, 2004). It also had a strong negative association with negative binge-watching experience and the motivation to watch for escapism, which is congruent with the fact that loss of control has been previously linked to problematic use of binge-watching (Dieterich et al, 2021). The present research thus supports the idea that self-control is a protective factor against more problematic forms of binge-watching (Granow et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…It was directly positively associated with well-being, which is congruent with its significant association with a variety of facets of well-being, including happiness (de Ridder et al, 2012; Tangney et al, 2004). It also had a strong negative association with negative binge-watching experience and the motivation to watch for escapism, which is congruent with the fact that loss of control has been previously linked to problematic use of binge-watching (Dieterich et al, 2021). The present research thus supports the idea that self-control is a protective factor against more problematic forms of binge-watching (Granow et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Finally, prior research has shown that individual differences predict binge-watching in various ways Valkenburg & Peter, 2013). Self-control, for example, is negatively associated with binge-watching (Dieterich et al, 2021;Riddle et al, 2018), while sensation seeking is associated with more bingewatching (Shim & Kim, 2018). Transportability ought to be associated with binge-watching, insofar as it predicts deriving stronger positive emotional experiences from media (Anghelcev et al, 2021).…”
Section: The Current Researchmentioning
confidence: 95%
See 2 more Smart Citations
“…That is to say, sensation seeking played a vital role in the risky decision of high risk‐takers. Nevertheless, some researchers revealed that high risk‐takers were insensitive to real loss (Dieterich et al, 2021; Sánchez‐Navarro et al, 2014; Xu et al, 2019). For instance, Sánchez‐Navarro et al (2014) revealed that compared to healthy controls, high risk‐takers, for example, the individuals with borderline personality disorder, were not sensitive to the value of the loss in the cups task.…”
mentioning
confidence: 99%